Hyperresistinemia – a Novel Feature in Systemic Infection During Human Pregnancy - Mazaki-Tovi, Shali (2010)
PROBLEM: Resistin, originally described as an adipokine, has emerged as a potent pro-inflammatory protein associated with both acute and chronic inflammation. Moreover, resistin has been proposed as a powerful marker of sepsis severity, as well as a predictor of survival of critically ill non-pregnant patients. The aim of this study was to determine whether pyelonephritis during pregnancy is associated with changes in maternal plasma resistin concentrations. METHODS OF STUDY: This cross-sectional study included the following groups: 1) normal pregnant women (n=85); and 2) pregnant women with pyelonephritis (n=40). Maternal plasma resistin concentrations were determined by ELISA. Non-parametric statistics were used for analyses. RESULTS: 1) The median maternal plasma resistin concentration was higher in patients with pyelonephritis than in those with a normal pregnancy (p<0.001); 2) among patients with pyelonephritis, the median maternal resistin concentration did not differ significantly between those with and without a positive blood culture (p=0.3); 3) among patients with pyelonephritis who were diagnosed with systemic inflammatory response syndrome (SIRS), those who fulfilled ≥3 criteria for SIRS had a significantly higher median maternal plasma resistin concentration than those who met only 2 criteria; and 4) maternal WBC count positively correlated with circulating resistin concentration (r=0.47, =0.02). CONCLUSIONS: Hyperresistinemia is a feature of acute pyelonephritis during pregnancy. The results of this study support the role of resistin as an acute-phase protein in the presence of bacterial infection during pregnancy.